2015
DOI: 10.1073/pnas.1503863112
|View full text |Cite
|
Sign up to set email alerts
|

Memory, scene construction, and the human hippocampus

Abstract: We evaluated two different perspectives about the function of the human hippocampus-one that emphasizes the importance of memory and another that emphasizes the importance of spatial processing and scene construction. We gave tests of boundary extension, scene construction, and memory to patients with lesions limited to the hippocampus or large lesions of the medial temporal lobe. The patients were intact on all of the spatial tasks and impaired on all of the memory tasks. We discuss earlier studies that assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 35 publications
(51 reference statements)
4
70
0
Order By: Relevance
“…It can also be seen as a system for enabling information from long-term memory to be rendered in parietal cortex as a coherent egocentric spatial scene consistent with a single viewpoint (Burgess et al, 2001;Byrne et al, 2007). This would explain the hippocampal role in imagery for spatial layout (Hassabis and Maguire, 2007;Schacter and Addis, 2007), but not for single objects (Kim et al, 2015). In either case, the hippocampal system can be used to generate information corresponding to upcoming states for use in planning, as consistent with recent experiments showing that self-generated place cell sequences do not necessarily reproduce the animal's most frequent behavior and instead sometimes generate paths never traversed by the animal (Gupta et al, 2010;Ó lafsdó ttir et al, 2015).…”
Section: Discussionsupporting
confidence: 67%
“…It can also be seen as a system for enabling information from long-term memory to be rendered in parietal cortex as a coherent egocentric spatial scene consistent with a single viewpoint (Burgess et al, 2001;Byrne et al, 2007). This would explain the hippocampal role in imagery for spatial layout (Hassabis and Maguire, 2007;Schacter and Addis, 2007), but not for single objects (Kim et al, 2015). In either case, the hippocampal system can be used to generate information corresponding to upcoming states for use in planning, as consistent with recent experiments showing that self-generated place cell sequences do not necessarily reproduce the animal's most frequent behavior and instead sometimes generate paths never traversed by the animal (Gupta et al, 2010;Ó lafsdó ttir et al, 2015).…”
Section: Discussionsupporting
confidence: 67%
“…Mullally et al (2012) found that patients with selective bilateral damage to hippocampus demonstrated less BE errors than control participants, supporting the role of hippocampus in BE. Inconsistent with this finding, Kim, Dede, Hopkins, and Squire (2015) found that amnestic patients with hippocampal damage exhibited BE similarly to healthy controls. Furthermore, Park, Intraub, Yi, Widders, and Chun (2007) demonstrated that BE task causes selective activation in the PPA, a region associated with processing scenes such as landscapes or buildings (Epstein & Kanwisher, 1998), but not in the Lateral Occipital Cortex, typically associated with object recognition (Grill-Spector et al, 1999).…”
Section: Introductionmentioning
confidence: 71%
“…Here, too, we localised HC using a working memory task, thus complementing previous studies that find evidence for HC recruitment across a range of cognitive tasks. Indeed, several studies of patients with HC atrophy have reported scene‐specific deficits for both memory and perceptual tasks [Bird et al, 2008; Hartley et al, 2007; Lee et al, 2005a, 2005b; Mullally et al, 2012; but see Kim et al, 2011, 2015]. Functional neuroimaging studies have likewise found group‐level HC activation during scene discrimination [Aly et al, 2013; Lee et al, 2008], scene construction/imagining [Zeidman et al, 2015], and working memory [Lee and Rudebeck, 2010b; Park et al, 2003].…”
Section: Discussionmentioning
confidence: 99%